PENGARUH PENERAPAN MODIFIKASI PERMAINAN BOLA VOLI TERHADAP HASIL BELAJAR PASING BAWAH DAN PASING DI SDI ILIGETANG - Timba, Frederiksen Novenrius Sini; Ritan, Paskalis Suban (Universitas Pendidikan Indonesia, 2021)
This study purposes to analyze the effect of skills on and through volleyball analysis techniques on student learning outcomes of class IVA SDI Iligetang, Beru, Alok Timur District. The research subjects of class VI A SDI Iligetang. The method used in pre-design research was one group pre-test post-test design. The results obtained were that the positive effect of the application of modification in volleyball to improve student learning outcomes was seen from changes in the pre-test and post-test scores where there was an increase from five students who passed the pre-test to twenty three students at the post-test stage. Modification of the volleyball game also positively affects the over and under passing skills of grade IV SDI Iligetang students, Beru, Alok Timur District, Sikka Regency, 2019/2020 Academic Year. The conclusion is that the volleyball game's modification is feasible to be used as alternative learning in improving student learning outcomes.